Assessment of the severity and incidence of Septoria tritici blotch (Zymoseptoria tritici) of wheat in Northwestern Ethiopia - Kassie, Molla Mekonnen; Dejene, Tiegist; Desta, Ermias Abate; Andualem, Mequanint; Tadesse, Wuletaw (Taylor & Francis, 2023)
Wheat is a global staple crop, which contributes 20% of the total dietary proteins and calories. Despite its importance, wheat production and productivity are affected by various biotic and abiotic stresses. Septoria leaf blotch is one of the biotic stresses that decreases production and grain quality. A field survey was conducted in twenty-four districts of Northwestern Ethiopia to figure out its distribution, inci dence, severity, and association with agronomic practices and agroecological factors. Logistic regression models were used to figure out associations of the disease intensity with independent variables. The highest mean disease incidence and severity were 90.7 and 46.67%. High severity and inci dence were associated with early planting, milk growth stage, and vertisol soil type. This shows that Septoria leaf blotch is a major biotic constraint for the study area. Therefore, effective, and suitable disease management options should be developed to improve the productivity of the crop in Northwestern Ethiopia.